2006
DOI: 10.1093/eurheartj/ehi816
|View full text |Cite
|
Sign up to set email alerts
|

Effects of metabolic modulation by trimetazidine on left ventricular function and phosphocreatine/adenosine triphosphate ratio in patients with heart failure

Abstract: Trimetazidine improves functional class and LV function in patients with heart failure. These effects are associated to the observed trimetazidine-induced increase in the PCr/ATP ratio, indicating preservation of the myocardial high-energy phosphate levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
149
2
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 211 publications
(159 citation statements)
references
References 39 publications
4
149
2
4
Order By: Relevance
“…In fact, artificial elevation of FFA in diabetic hearts reduces cardiac efficiency via an oxygen waste for noncontractile purposes (26). This scenario was supported by our finding in patients with heart failure in whom treatment with Trimetazidine, a partial fatty acids oxidation inhibitor, induced improvement of the LV function and PCr/ ATP ratio (27), likely switching the energy substrate preference (28). Hence, we may speculate that in patients with overt type 2 diabetes, the increased FFAs availability, pushing their own oxidative disposal, induces a detrimental and proportional effect on the PCr-to-ATP ratio (6).…”
Section: Effects Of Hemodynamic and Metabolic Variables On The Correlmentioning
confidence: 59%
“…In fact, artificial elevation of FFA in diabetic hearts reduces cardiac efficiency via an oxygen waste for noncontractile purposes (26). This scenario was supported by our finding in patients with heart failure in whom treatment with Trimetazidine, a partial fatty acids oxidation inhibitor, induced improvement of the LV function and PCr/ ATP ratio (27), likely switching the energy substrate preference (28). Hence, we may speculate that in patients with overt type 2 diabetes, the increased FFAs availability, pushing their own oxidative disposal, induces a detrimental and proportional effect on the PCr-to-ATP ratio (6).…”
Section: Effects Of Hemodynamic and Metabolic Variables On The Correlmentioning
confidence: 59%
“…Inhibition of this enzyme decreases fatty acid oxidation, which then stimulates glucose oxidation and inhibits glycolysis. These TMZ-induced chain effects increase the creatine phosphate/ATP ratio by a significant 33%, indicating preservation of myocardial high-energy phosphate levels and ion pump function, which translates into improved cardiac efficiency and reduced symptoms [38]. These effects no doubt account for the real-world benefits our study has shown with add-on TMZ …”
Section: Discussionmentioning
confidence: 58%
“…In patients with ischemic cardiomy opathy, a previous acute myocardial infarction, multivessel coronary artery disease and ventricular dysfunction (ejection fraction 33%), trimetazidine therapy (2 months) improved contractile response to lowdose dobutamine in chronically dysfunc tional myocardium. Fragasso et al demonstrated that trimetazidine restored the energetic status of myocardium in patients with heart failure [18]. In these patients, the phosphocreatine and adenosine triphosphate (PCr:ATP) ratio, an important index of energetic status, was similar to that in healthy individuals and significantly improved compared with that in a placebo group.…”
Section: Editorialmentioning
confidence: 97%